ENERGY TRANSFORMATION AND ECONOMIC GROWTH IN INDONESIA: TO MEASURE THE IMPACT OF RENEWABLE AND NON-RENEWABLE ENERGY - Hutajulu, Dinar Melani; Indrawati, Lucia Rita (Jurnal REP (Riset Ekonomi Pembangunan), 2023)
The research aims to see the impact of renewable energy, if it is compared to non-renewable energy in increasing economic growth in Indonesia, over the last few decades, find out the impact of the energy transition that is designated to support sustainable economic growth, and to identify whether non-renewable energy still has a more favorable impact on growth of Indonesian economy. The research employs Indonesian secondary data from 2000 – 2022 that illustrates economic growth, biomass energy, natural gas, oil, fuel, and electricity variables. Data obtained from the publication released by Statistics Indonesia and the Ministry of Energy and Mineral Resources. Error Correction Model (ECM) is utilized as the analysis tool. The findings suggest that traditional biomass renewable energy has no impact on achieving the expected economic growth in Indonesia as a result of the minimal availability of biomass waste. Meanwhile, natural gas does not have the potential to increase economic growth due to the lack of infrastructure and management of this energy. Oil fuel contributes to reducing economic growth as a result of dwindling availability, fluctuating prices, and high subsidy costs. While electricity drives economic growth, its availability is still far from meeting people's consumption needs. Government policy needs to target the availability of this energy, especially encouraging the production of electricity sourced from available natural resources (renewable).